High-antibacterial silver-doped nano-silicon oxide composite material and preparation method thereof

CN122910977APending Publication Date: 2026-10-16XUANCHENG JINGRUI NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610517979.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种高抗菌性掺银纳米氧化硅复合材料及其制备方法,通过在单宁酸骨架上引入烯丙基双键并利用巯基-烯点击化学反应将改性单宁酸-银纳米颗粒共价键合在巯基化二氧化硅表面,有效解决了现有技术中银纳米颗粒与载体结合力弱、易脱落团聚及长效抗菌性能不佳的问题,所得材料具有高抗菌活性、高稳定性及广谱抗菌性,适用于高端医疗、食品包装及环境治理等领域

Benefits of technology

1、本发明通过改性单宁酸-银纳米颗粒与巯基化二氧化硅之间的巯基-烯点击化学反应,构建了以共价键连接的稳定复合结构,有效解决了银纳米颗粒在长期使用或复杂环境中易从载体脱落、迁移和团聚的问题,所得复合材料不仅具有优异的初始抗菌活性,更显著提升了其长效抗菌性能、结构稳定性及在动态或苛刻环境下的使用可靠性,为高性能抗菌材料的开发提供了新思路。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1776649931453-000001
    Figure REF-OBJ-1776649931453-000001
Patent Text Reader

Abstract

The application discloses a kind of high antibacterial silver-doped nano-silicon oxide composite materials and preparation method thereof, belong to antibacterial material technical field, first by allyl glycidyl ether modified tannic acid, with it as reducing agent and stabilizer in situ reduction silver ammonia solution, prepared modified tannic acid-silver nanoparticle dispersion, finally again with mercapto silica in oxidation-reduction initiation system through click chemistry reaction, obtain high antibacterial composite material;The application introduces allyl double bond on the tannic acid skeleton and utilizes mercapto-alkene click chemistry reaction, and the modified tannic acid-silver nanoparticle is covalently bonded on the surface of mercapto silica, effectively solve the problems that silver nanoparticle and carrier binding force are weak in the prior art, easy to fall off and agglomerate and long-acting antibacterial performance is poor, the obtained material has high antibacterial activity, high stability and broad-spectrum antibacterial activity, and is suitable for high-end medical, food packaging and environmental governance and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of antibacterial materials technology, specifically a high antibacterial silver-doped nano-silica composite material and its preparation method. Background Technology

[0002] In fields such as medical and health care, food packaging, and environmental governance, the research and application of antimicrobial materials are becoming increasingly important. Among them, silver-based antimicrobial agents have become the mainstream of research and application in this field due to their significant advantages such as broad-spectrum antimicrobial activity and difficulty in inducing bacterial resistance. Nano-silica, as an inorganic material with stable chemical properties, non-toxicity, large specific surface area, and controllable morphology, is an ideal carrier for loading silver nanoparticles. It can not only effectively disperse silver nanoparticles and inhibit their aggregation, but also achieve controlled and sustained release of silver ions by regulating the carrier structure, thereby significantly improving the durability and safety of antimicrobial materials. It shows broad prospects in the development of high-performance antimicrobial composite materials.

[0003] However, in traditional processes, uneven carrier structure and insufficient specific surface area often lead to low initial silver loading and poor dispersion, which in turn affects the initial antibacterial performance. To address this issue, Chinese patent application CN111644146A discloses a method for preparing silver-loaded nano-silica antibacterial materials. This method optimizes the sol-gel process to prepare a porous nano-silica carrier with high specific surface area and regular pore structure. It also utilizes glucose to reduce silver ions in situ under alkaline conditions to load the generated nano-silica particles into the carrier pores, while introducing titanium dioxide to enhance the antibacterial effect.

[0004] However, this approach mainly relies on physical adsorption to load silver nanoparticles into the pores of silica. This combination of physical mixing and weak interaction can lead to silver nanoparticles easily detaching from the carrier surface, migrating, or agglomerating uncontrollably under long-term use or complex environmental conditions. This not only reduces the long-term antibacterial properties of the material, but may also cause secondary pollution or local toxicity risks due to the loss of silver particles, limiting the use of this type of material in high-end application scenarios that require long-term stability and high reliability. Summary of the Invention

[0005] The purpose of this invention is to provide a high-antibacterial silver-doped nano-silica composite material and its preparation method. By introducing allyl double bonds into the tannic acid backbone and using a mercapto-alkene click chemistry reaction to covalently bond modified tannic acid-silver nanoparticles onto the surface of mercapto-silica, the problems of weak bonding force between silver nanoparticles and carriers, easy detachment and aggregation, and poor long-term antibacterial performance in the prior art are effectively solved. The resulting material has high antibacterial activity, high stability and broad-spectrum antibacterial properties, and is suitable for high-end medical, food packaging and environmental remediation fields.

[0006] The objective of this invention can be achieved through the following technical solutions: A method for preparing a highly antibacterial silver-doped nano-silica composite material includes the following steps: Step 1: The allyl double bond is grafted onto the tannic acid skeleton through a nucleophilic ring-opening reaction to obtain modified tannic acid.

[0007] Step 2: Using modified tannic acid as a reducing agent, Ag is reduced in situ. + The silver was reduced to elemental silver and loaded in situ onto the modified tannic acid framework to obtain a modified tannic acid-silver nanoparticle dispersion.

[0008] Step 3: Modified tannic acid-silver nanoparticles are covalently bonded to the surface of mercapto-silica through a mercapto-olefin chemical reaction to obtain a highly antibacterial silver-doped silica nanocomposite material.

[0009] Furthermore, the specific preparation steps of the highly antibacterial silver-doped nano-silica composite material are as follows: Under nitrogen protection, mercapto-modified silica, modified tannic acid-silver nanoparticle dispersion, and anhydrous ethanol were added to a reaction vessel and stirred for 25-35 min. The pH of the system was adjusted to 5.8-6.2 with sodium hydroxide. The reaction was carried out at 30-40℃ and 250-350 r / min. Ammonium persulfate and sodium bisulfite were added, and the mixture was stirred and refluxed for 4-6 h. After the reaction was completed, the mixture was washed and dried to obtain a highly antibacterial silver-doped silica nanocomposite material.

[0010] Furthermore, the ratio of mercapto-modified silica, modified tannic acid-silver nanoparticle dispersion, anhydrous ethanol, ammonium persulfate, and sodium bisulfite is 4.5-5.5g: 45-55mL: 45-55mL: 0.08-0.12g: 0.04-0.06g.

[0011] Furthermore, the specific preparation steps of the modified tannic acid-silver nanoparticle dispersion are as follows: An 80 mM silver nitrate solution and ammonia solution with a concentration of 0.175 g / mL were added to a reaction vessel and stirred at 250-350 r / min and 20-30℃ until homogeneous. Under nitrogen protection, a modified tannic acid solution was slowly added to the reaction vessel, and the reaction was continued under the same conditions for 1 h. After dialyzing for 24-48 h, the volume was adjusted to 100 mL with deionized water to obtain a modified tannic acid-silver nanoparticle dispersion.

[0012] Furthermore, the volume ratio of silver nitrate solution, ammonia water, and modified tannic acid solution is 8-12:4-6:4-6.

[0013] Furthermore, the modified tannic acid solution is obtained by mixing modified tannic acid and a 5% NaOH solution at a ratio of 0.2-0.3g:4-6mL.

[0014] Furthermore, the specific preparation steps for modified tannic acid are as follows: Tannic acid and allyl glycidyl ether were added to a reaction vessel and stirred at 250-350 r / min and 75-85℃ until homogeneous. A 10% NaOH aqueous solution was slowly added dropwise to the reaction vessel, and the reaction was continued at a constant temperature with stirring for 2.5-3.5 h. After washing, the mixture was distilled under reduced pressure to obtain modified tannic acid.

[0015] Furthermore, the mass ratio of tannic acid, allyl glycidyl ether, and NaOH aqueous solution is 8-12:9-13:8-12.

[0016] Furthermore, the specific steps for mercaptolated silica are as follows: 3-Mercaptopropyltriethoxysilane and anhydrous ethanol were added to a reaction vessel and stirred at 20-30°C and 250-350 rpm until dissolved. Then, deionized water was slowly added dropwise to the reaction vessel, and stirring was continued at room temperature for 25-35 min. Nano-silica was then added to the reaction vessel, and the mixture was stirred and refluxed at 55-65°C and 250-350 rpm for 3.5-4.5 h. After the reaction was completed, the mixture was cooled, filtered, washed, and dried to obtain mercapto-based silica.

[0017] Furthermore, the ratio of 3-mercaptopropyltriethoxysilane, anhydrous ethanol, deionized water, and nano-silica is 0.4-0.6g: 180-220mL: 1-2mL: 4.5-5.5g.

[0018] The beneficial effects of this invention are: 1. This invention constructs a stable composite structure linked by covalent bonds through a click chemical reaction between modified tannic acid-silver nanoparticles and mercapto-alkenylated silica. This effectively solves the problem of silver nanoparticles easily detaching from the carrier, migrating, and agglomerating during long-term use or in complex environments. The resulting composite material not only has excellent initial antibacterial activity, but also significantly improves its long-term antibacterial performance, structural stability, and reliability in dynamic or harsh environments, providing a new approach for the development of high-performance antibacterial materials.

[0019] 2. The modified tannic acid prepared by this invention and the silver nanoparticle dispersion obtained therefrom have multiple beneficial effects: First, the phenolic hydroxyl groups retained in the modified tannic acid can efficiently reduce silver ammonia ions under mild conditions. At the same time, the macromolecular structure of tannic acid, as an excellent steric hindrance stabilizer, can effectively coat and stabilize silver nanoparticles, preventing their oxidation and aggregation, thus realizing the in-situ synthesis and anti-aggregation dispersion of silver nanoparticles. Second, the double bonds introduced through allyl modification enable tannic acid to have both reducing / stabilizing functions and click chemistry reactivity, becoming a multifunctional molecular bridge connecting silver particles and the carrier. Finally, the antibacterial and antioxidant activities of tannic acid itself and the antibacterial effect of silver nanoparticles produce a synergistic effect, forming a highly efficient and stable composite antibacterial unit.

[0020] 3. In this invention, the synergistic effect of thiolized silica and the redox initiation system achieves efficient and stable loading of silver nanoparticles in the composite material: by thiolizing the silica surface, a high density of thiol functional groups is introduced, providing sufficient active anchoring sites for subsequent click chemical bonding; at the same time, the redox initiation system composed of ammonium persulfate and sodium bisulfite can efficiently initiate thiol-alkene click chemical reactions under mild conditions, forming strong CSC covalent bonds between modified tannic acid and thiolized silica, thereby upgrading the silver nanoparticles from traditional physical adsorption to chemical anchoring, significantly enhancing the bonding strength, structural stability and washability of the composite material. In addition, this covalent bond network can also extend the antibacterial life through the degradation of tannic acid or responsive regulation of the slow-release behavior of silver ions.

[0021] Furthermore, the sulfate radicals generated by the decomposition of ammonium persulfate not only act as highly efficient initiators to promote the click reaction, but the residual sulfate ions may also help maintain the dispersion stability of silver nanoparticles by adjusting the ionic strength and balancing the charge of the system. Detailed Implementation

[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0023] Example 1: A highly antibacterial silver-doped nano-silica composite material, comprising the following steps: S1: Add 10g of tannic acid (TA) and 11g of allyl glycidyl ether (AGE) to the reactor and stir until homogeneous at 300r / min and 80℃. Slowly add 10g of 10% NaOH aqueous solution to the reactor and continue stirring at a constant temperature for 3h. Wash with deionized water until the final wash solution is neutral. Finally, remove impurities by vacuum distillation to obtain modified tannic acid.

[0024] A basic catalytic nucleophilic ring-opening modification method was adopted, which utilizes the phenolic hydroxyl groups abundant in tannic acid molecules to undergo a nucleophilic ring-opening reaction with the epoxy groups in allyl glycidyl ether, thereby introducing reactive allyl double bonds into the tannic acid molecular skeleton, and finally obtaining modified tannic acid.

[0025] S2: 0.25 g of modified tannic acid and 5 mL of 5% NaOH solution were added to a stirred tank and ultrasonically treated at 300 r / min and 25 °C to obtain a modified tannic acid solution. 10 mL of 80 mM silver nitrate solution and 5 mL of 0.175 g / mL ammonia solution were added to a reaction vessel and stirred evenly at 300 r / min and 25 °C. Then, under nitrogen protection, 5 mL of the modified tannic acid solution was slowly added to the reaction vessel and stirred for 1 h at 300 r / min and 25 °C. After dialyzing with deionized water for 36 h and bringing the volume to 100 mL with deionized water, a modified tannic acid-silver nanoparticle dispersion was obtained.

[0026] An in-situ reduction method under alkaline conditions was employed, utilizing the solubility of modified tannic acid in alkaline solution. The phenolic hydroxyl groups retained in the molecule act as both reducing agents and stabilizers, reacting with the silver ammonia complex ions ([Ag(NH3)2]) in the silver ammonia solution. + A redox reaction occurs, transforming Ag... + The modified tannic acid-silver nanoparticles were reduced to uniformly distributed elemental silver nanoparticles with a particle size of 10-50 nm and then loaded in situ onto a modified tannic acid framework, ultimately yielding a modified tannic acid-silver nanoparticle dispersion with good dispersibility and antibacterial activity.

[0027] S3: 0.5 g of 3-mercaptopropyltriethoxysilane (MPTMS) and 200 mL of anhydrous ethanol were added to a reaction vessel and stirred until dissolved at 25 °C and 300 r / min. Then, 1.5 mL of deionized water was slowly added dropwise to the reaction vessel, and stirring was continued at room temperature for 30 min. Then, 5 g of nano-silica (100 nm in size) was added to the reaction vessel, and the mixture was stirred and refluxed at 60 °C and 300 r / min for 4 h. After the reaction was completed, the mixture was cooled to room temperature, and the product was filtered and washed with deionized water and anhydrous ethanol in sequence. Finally, it was dried under vacuum at 60 °C for 10 h to obtain mercapto-modified silica.

[0028] S4: Under nitrogen protection, 5g of mercapto-modified silica, 50mL of modified tannic acid-silver nanoparticle dispersion and 50mL of anhydrous ethanol were added to the reactor and stirred for 30min. The pH of the system was adjusted to 6 with sodium hydroxide. Under the conditions of 35℃ and 300r / min, 0.1g of ammonium persulfate and 0.05g of sodium bisulfite were added and the mixture was stirred and refluxed for 5h. After the reaction was completed, the mixture was washed with deionized water and finally dried under vacuum at 60℃ for 10h to obtain a high antibacterial silver-doped silica nanocomposite material.

[0029] By utilizing the reaction of ammonium persulfate and sodium bisulfite to generate free radicals, the thiol groups on the surface of thiolized silica and the allyl double bonds on the modified tannic acid-silver nanoparticles are activated, resulting in a thiol-alkene free radical click covalent grafting reaction. This forms a CSC covalent bond between the two, achieving stable immobilization and uniform dispersion of silver nanoparticles on the silica surface. Ultimately, a highly antibacterial silver-doped silica nanocomposite material is prepared, with thiolized silica as the rigid framework and a layer of modified tannic acid organic functional layer uniformly encapsulating silver nanoparticles grafted onto the surface via covalent bonds.

[0030] Example 2: A highly antibacterial silver-doped nano-silica composite material, comprising the following steps: S1: Add 8g of tannic acid (TA) and 9g of allyl glycidyl ether (AGE) to the reactor and stir until homogeneous at 250r / min and 75℃. Slowly add 8g of 10% NaOH aqueous solution to the reactor and continue stirring at a constant temperature for 2.5h. Wash with deionized water until the final wash solution is neutral. Finally, remove impurities by vacuum distillation to obtain modified tannic acid.

[0031] S2: 0.2 g of modified tannic acid and 4 mL of 5% NaOH solution were added to a stirred tank and ultrasonically treated at 2500 r / min and 20 °C to obtain a modified tannic acid solution. 8 mL of 80 mM silver nitrate solution and 4 mL of 0.175 g / mL ammonia solution were added to a reaction vessel and stirred evenly at 250 r / min and 20 °C. Then, under nitrogen protection, 4 mL of the modified tannic acid solution was slowly added to the reaction vessel, and the reaction was continued under the same conditions for 1 h. After dialyzing with deionized water for 24 h and adjusting the volume to 100 mL with deionized water, a modified tannic acid-silver nanoparticle dispersion was obtained.

[0032] S3: 0.4 g of 3-mercaptopropyltriethoxysilane (MPTMS) and 180 mL of anhydrous ethanol were added to a reaction vessel and stirred until dissolved at 20 °C and 250 r / min. Then, 1 mL of deionized water was slowly added dropwise to the reaction vessel, and stirring was continued at room temperature for 25 min. Then, 4.5 g of nano-silica (100 nm in size) was added to the reaction vessel, and the mixture was stirred and refluxed at 55 °C and 250 r / min for 3.5 h. After the reaction was completed, the mixture was cooled to room temperature, and the product was filtered and washed with deionized water and anhydrous ethanol in sequence. Finally, it was dried under vacuum at 60 °C for 10 h to obtain mercapto-modified silica.

[0033] S4: Under nitrogen protection, 4.5 g of mercapto-modified silica, 45 mL of modified tannic acid-silver nanoparticle dispersion and 45 mL of anhydrous ethanol were added to the reactor and stirred for 25 min. The pH of the system was adjusted to 5.8 with sodium hydroxide. Under the conditions of 30 °C and 250 r / min, 0.08 g of ammonium persulfate and 0.04 g of sodium bisulfite were added and the mixture was stirred and refluxed for 4 h. After the reaction was completed, the mixture was washed with deionized water and finally dried under vacuum at 60 °C for 10 h to obtain a high antibacterial silver-doped silica nanocomposite material.

[0034] Example 3: A highly antibacterial silver-doped nano-silica composite material, comprising the following steps: S1: Add 12g of tannic acid (TA) and 13g of allyl glycidyl ether (AGE) to a reaction vessel and stir until homogeneous at a speed of 350r / min and a temperature of 85℃. Slowly add 12g of 10% NaOH aqueous solution to the reaction vessel and continue stirring at a constant temperature for 3.5h. Wash with deionized water until the final washing solution is neutral. Finally, remove impurities by vacuum distillation to obtain modified tannic acid.

[0035] S2: 0.3g of modified tannic acid and 6mL of 5% NaOH solution were added to a stirred tank and ultrasonically treated at 350r / min and 30℃ to obtain a modified tannic acid solution. 12mL of 80mM silver nitrate solution and 6mL of 0.175g / mL ammonia solution were added to a reaction vessel and stirred evenly at 350r / min and 20-30℃. Then, under nitrogen protection, 6mL of the modified tannic acid solution was slowly added to the reaction vessel and stirred for 1h under the same conditions. After dialyzing with deionized water for 48h and adjusting the volume to 100mL with deionized water, a modified tannic acid-silver nanoparticle dispersion was obtained.

[0036] S3: 0.6 g of 3-mercaptopropyltriethoxysilane (MPTMS) and 220 mL of anhydrous ethanol were added to a reaction vessel and stirred until dissolved at 30 °C and 350 r / min. Then, 2 mL of deionized water was slowly added dropwise to the reaction vessel, and stirring was continued at room temperature for 35 min. Then, 5.5 g of nano-silica (100 nm in size) was added to the reaction vessel, and the mixture was stirred and refluxed at 65 °C and 350 r / min for 4.5 h. After the reaction was completed, the mixture was cooled to room temperature, and the product was filtered and washed with deionized water and anhydrous ethanol in sequence. Finally, it was dried under vacuum at 60 °C for 10 h to obtain mercapto-modified silica.

[0037] S4: Under nitrogen protection, 5.5 g of mercapto-modified silica, 55 mL of modified tannic acid-silver nanoparticle dispersion and 55 mL of anhydrous ethanol were added to a reaction vessel and stirred for 35 min. The pH of the system was adjusted to 6.2 with sodium hydroxide. Under the conditions of 40 °C and 350 r / min, 0.12 g of ammonium persulfate and 0.06 g of sodium bisulfite were added and the mixture was stirred and refluxed for 6 h. After the reaction was completed, the mixture was washed with deionized water and finally dried under vacuum at 60 °C for 10 h to obtain a high antibacterial silver-doped silica nanocomposite material.

[0038] Comparative Example 1: Based on Example 1, the addition of initiators ammonium persulfate and sodium bisulfite in step S4 was omitted. 5g of mercapto-modified silica, 50mL of modified tannic acid-silver nanoparticle dispersion and 50mL of anhydrous ethanol were added to the reactor and stirred for 4-6h at a speed of 300r / min and a temperature of 30-40℃, so that it could only combine through physical mixing and possible weak interactions. All other steps and parameters remained unchanged, and silver-doped silica nanoparticle composite material was obtained.

[0039] Comparative Example 2: Based on Example 1, step S1 was omitted, and in step S2, ordinary tannic acid of equal mass was directly replaced with modified tannic acid, while all other steps and parameters remained unchanged, to obtain silver-doped nano-silica composite material.

[0040] Comparative Example 3: Based on Example 1, step S3 was omitted, and in step S4, an equal mass of unmodified nano-silica was used to replace mercaptoized silica, while all other steps and parameters remained unchanged, to obtain a silver-doped nano-silica composite material.

[0041] The silver-doped nano-silica composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests. The antibacterial effect of the test samples was tested with an oscillation contact time of 24 hours in accordance with the ASTM E 2149-2020Z standard. The evaluation criteria were: antibacterial rate ≥90%, the product has strong antibacterial activity; antibacterial rate ≥50%, the product has antibacterial activity; antibacterial rate <50%, the product has no antibacterial activity.

[0042] The results are shown in Table 1: Table 1 Performance test results of various silver-doped nano-silica composite materials As shown in Table 1, the silver-doped nano-silica composite materials prepared in Examples 1-3 of this invention exhibit excellent antibacterial properties. In tests against three typical bacterial species—Staphylococcus aureus (ATCC 6538), Candida albicans (ATCC 1021), and Escherichia coli (ATCC 25922)—the antibacterial rates all approached or reached 99%, meeting the standard of strong antibacterial activity with an antibacterial rate ≥90%. Furthermore, the performance differences among the three species were small, indicating that the process of this invention is stable and possesses good broad-spectrum antibacterial ability and repeatability.

[0043] In Comparative Example 1, the key initiator of the click chemistry reaction was omitted in step S4, resulting in the silver nanoparticles and the carrier relying solely on physical adsorption. The antibacterial rate decreased significantly to 64.11%-65.45%. Although it still met the antibacterial activity standard (≥50%), it was significantly different from Example 1. This indicates that the covalent bonds formed by the thiol-alkene click chemistry are the key to improving the loading strength and long-lasting antibacterial properties of silver particles.

[0044] Comparative Example 2 omitted the tannic acid modification step and used ordinary tannic acid instead of modified tannic acid, which resulted in the inability to effectively participate in the subsequent click reaction, reduced the binding force of silver particles, and decreased the antibacterial rate to 55.67%-60.14%. Compared with Example 1, its antibacterial effect on the three bacterial species was significantly weakened, proving that the double bond structure introduced by tannic acid modification can effectively construct a highly efficient antibacterial system.

[0045] Comparative Example 3 omitted the thiolization modification of silica and directly used raw SiO2, which resulted in the ineffective conduct of the click reaction, uneven dispersion of silver particles and poor binding force, with an antibacterial rate of only 50.89%-54.76%, close to the threshold of no antibacterial activity. This result indicates that thiolized silica, as a reaction carrier and anchoring point, is the core component for achieving efficient loading and stable release of silver nanoparticles.

[0046] It should be noted that, in this document, terms such as “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0047] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention.

Claims

1. A method for preparing a highly antibacterial silver-doped nano-silica composite material, characterized in that, Includes the following steps: Step 1: The allyl double bond is grafted onto the tannic acid skeleton through a nucleophilic ring-opening reaction to obtain modified tannic acid; Step 2: Using modified tannic acid as a reducing agent, Ag is reduced in situ. + The modified tannic acid-silver nanoparticle dispersion was obtained by reducing it to elemental silver and loading it in situ onto the modified tannic acid framework. Step 3: Modified tannic acid-silver nanoparticles are covalently bonded to the surface of mercapto-silica through a mercapto-olefin chemical reaction to obtain a highly antibacterial silver-doped silica nanocomposite material.

2. The method for preparing a highly antibacterial silver-doped nano-silica composite material according to claim 1, characterized in that, The specific preparation steps of the highly antibacterial silver-doped nano-silica composite material are as follows: Under nitrogen protection, mercapto-modified silica, modified tannic acid-silver nanoparticle dispersion, and anhydrous ethanol were added to a reaction vessel and stirred for 25-35 min. The pH of the system was adjusted to 5.8-6.2 with sodium hydroxide. The reaction was carried out at 30-40℃ and 250-350 r / min. Ammonium persulfate and sodium bisulfite were added, and the mixture was stirred and refluxed for 4-6 h. After the reaction was completed, the mixture was washed and dried to obtain a highly antibacterial silver-doped silica nanocomposite material.

3. The method for preparing a highly antibacterial silver-doped nano-silica composite material according to claim 1, characterized in that, The ratio of mercapto-modified silica, modified tannic acid-silver nanoparticle dispersion, anhydrous ethanol, ammonium persulfate, and sodium bisulfite is 4.5-5.5g: 45-55mL: 45-55mL: 0.08-0.12g: 0.04-0.06g.

4. The method for preparing a highly antibacterial silver-doped nano-silica composite material according to claim 2, characterized in that, The specific preparation steps of the modified tannic acid-silver nanoparticle dispersion are as follows: An 80 mM silver nitrate solution and ammonia solution with a concentration of 0.175 g / mL were added to a reaction vessel and stirred at 250-350 r / min and 20-30℃ until homogeneous. Under nitrogen protection, a modified tannic acid solution was slowly added to the reaction vessel, and the reaction was continued under the same conditions for 1 h. After dialyzing for 24-48 h, the volume was adjusted to 100 mL with deionized water to obtain a modified tannic acid-silver nanoparticle dispersion.

5. The method for preparing a highly antibacterial silver-doped nano-silica composite material according to claim 4, characterized in that, The volume ratio of the silver nitrate solution, ammonia, and modified tannic acid solution is 8-12:4-6:4-6.

6. The method for preparing a highly antibacterial silver-doped nano-silica composite material according to claim 4, characterized in that, The modified tannic acid solution is obtained by mixing modified tannic acid and 5% NaOH solution at a ratio of 0.2-0.3g:4-6mL.

7. The method for preparing a highly antibacterial silver-doped nano-silica composite material according to claim 6, characterized in that, The specific preparation steps of the modified tannic acid are as follows: Tannic acid and allyl glycidyl ether were added to a reaction vessel and stirred at 250-350 r / min and 75-85℃ until homogeneous. A 10% NaOH aqueous solution was slowly added dropwise to the reaction vessel, and the reaction was continued at a constant temperature with stirring for 2.5-3.5 h. After washing, the mixture was distilled under reduced pressure to obtain modified tannic acid.

8. The method for preparing a highly antibacterial silver-doped nano-silica composite material according to claim 7, characterized in that, The mass ratio of tannic acid, allyl glycidyl ether, and NaOH aqueous solution is 8-12:9-13:8-12.

9. The method for preparing a highly antibacterial silver-doped nano-silica composite material according to claim 1, characterized in that, The specific steps for the mercaptoized silicon dioxide are as follows: 3-Mercaptopropyltriethoxysilane and anhydrous ethanol were added to a reaction vessel and stirred at 20-30℃ and 250-350 r / min until dissolved. Then, deionized water was slowly added dropwise to the reaction vessel, and stirring was continued at room temperature for 25-35 min. Nano-silica was then added to the reaction vessel, and the mixture was stirred and refluxed at 55-65℃ and 250-350 r / min for 3.5-4.5 h. After the reaction was completed, the mixture was cooled, filtered, washed, and dried to obtain mercapto-based silica. The ratio of 3-mercaptopropyltriethoxysilane, anhydrous ethanol, deionized water, and nano-silica is 0.4-0.6g: 180-220mL: 1-2mL: 4.5-5.5g.

10. A highly antibacterial silver-doped nano-silica composite material, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of nano silicon dioxide silver-loaded antibacterial material

    CN111644146A